Human Rights Analysis of Traditional and Formal Transitional Justice in Rwanda: Case of Gacaca - Seyyed Ghasem Zamani; Yousef Babaei Dashlibroon (پژوهشهای حقوقی)
Following the genocide in Rwanda that killed one million people, the Rwandan government turned to Gacaca courts, which are rooted in the culture of all the people of Rwanda, in order to expedite the prosecution of those involved in this humanitarian catastrophe and reduce the prison population. In order to adapt these courts to the conditions of the crimes committed, the Rwandan government made several changes in these courts, which according to many, changed its traditional and informal nature and brought it closer to the criminal courts. This intermediate mechanism, in addition to having gains and advantages as an alternative judicial response, has also caused concern and criticism from a human rights perspective. The present article examines this intermediate mechanism and its positive and negative aspects from a human rights perspective.